2008
DOI: 10.1242/jcs.033522
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor complex AP-2 regulates post-endocytic trafficking through the non-clathrin Arf6-dependent endocytic pathway

Abstract: The ADP-ribosylation factor 6 (Arf6) GTPase functions as a key regulator of endocytic trafficking, participating in clathrin-independent endocytosis in most cell types. Unexpectedly, we found that siRNA-mediated depletion of clathrin or of adaptor protein 2 (AP-2)-complex subunits alters trafficking of Arf6 pathway cargo proteins, such as major histocompatibility complex class I (MHCI) and β1 integrin. Internalization of these cargoes from the plasma membrane was not affected in cells depleted of clathrin, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…This suggests that the Numb interaction with AP-2 is important for the post-endocytic trafficking of Notch1. In keeping with this notion, a role for AP-2 in the post-endocytic trafficking of cargo through a clathrin-independent pathway has recently been described (61).…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that the Numb interaction with AP-2 is important for the post-endocytic trafficking of Notch1. In keeping with this notion, a role for AP-2 in the post-endocytic trafficking of cargo through a clathrin-independent pathway has recently been described (61).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, Arf6 mainly localizes at the plasma membrane, where it is involved in a wide variety of cellular events. These cellular events include actin cytoskeleton reorganization (Song et al, 1998;Honda et al, 1999), regulation of adherens junctions (Palacios et al, 2001), clathrin-mediated endocytosis (Radhakrishna and Donaldson, 1997;Altschuler et al, 1999;Radhakrishna et al, 1999), phagocytosis (Zhang et al, 1998;Uchida et al, 2001), exocytosis (Galas et al, 1997;Vitale et al, 2002), and post-endocytic vesicle trafficking (Lau and Chou, 2008). Thus, cellular events, in which Arf6 is involved, differ from those regulated by other members of the Arf family.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that some of these pathways differ only slightly from each other, and certain endocytic components can participate in more than just one pathway (35,41,55). Most of the research carried out on enterovirus endocytosis has been done with echovirus 1 (EV1), coxsackievirus B3 (CBV3), and poliovirus (PV).…”
mentioning
confidence: 99%